Analysis of the Influence of Product Innovation, Product Price, and Product Quality on Consumer Purchasing Decisions for Medan Pancing Mie Gacoan - Pane, Sari Aparpan; Syahreza, Dina Sarah; Yumni, Raihanah; Simanjuntak, Stephen; Marpaung, Jeremy; Prabowo, Stevanus Wahyudianto (Lembaga Riset Mutiara Akbar (LARISMA), 2024)
The fastfood culinary industry in Indonesia is experiencing rapid growth, offering a variety of attractive food options for the community. One of the popular types of food is instant noodles, especially fried instant noodles made by the Mie Gacoan brand. This study aims to analyze the relationship between Product Innovation, Product Price, and Product Quality on Purchase Decisions for Mie Gacoan Medan Pancing. The research method used is quantitative, with data collection techniques through surveys. Data were analyzed using multiple linear regression. The results show that product innovation, product price, and product quality have a positive and significant effect on purchase decisions. Additionally, product innovation, product price, and product quality also have a simultaneous effect on purchase decisions. This study provides important implications for Mie Gacoan Medan Pancing, where Mie Gacoan Medan Pancing must continuously innovate by introducing new and attractive high-quality products for consumers, and also consider their product prices to remain competitive and affordable for consumers.